2012
DOI: 10.1158/1055-9965.epi-12-0458
|View full text |Cite
|
Sign up to set email alerts
|

Variation in IL10 and Other Genes Involved in the Immune Response and in Oxidation and Prostate Cancer Recurrence

Abstract: Background To evaluate the association of variation in genes involved in immune response, including IL10, production and detoxification of reactive oxygen species, and repair of oxidative DNA damage with risk of recurrence after surgery for localized prostate cancer. Methods We conducted a nested case-control study of men who had a radical prostatectomy in 1993–2001. 484 recurrence cases and 484 controls were matched on age, race, and pathologic stage and grade. Germline DNA was extracted from paraffin-embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 37 publications
2
55
0
Order By: Relevance
“…This suggests that unrepaired DNA damage could induce systemic induction of the immunosuppressive cytokine. Additional evidence suggests that IL10 single nucleotide polymorphism (SNP) variants are associated with basal cell carcinoma alongside with DNA repair gene variants and also with genes such as iNOS that is associated with prostate cancer recurrence (Dluzniewski et al , 2012; Festa et al , 2005). Since the relationship between IL10 and the DNA damage response is unclear, future studies will require molecular and biochemical characterization of this pathway.…”
Section: Tumor Microenvironment Inflammation and Dna Repairmentioning
confidence: 99%
“…This suggests that unrepaired DNA damage could induce systemic induction of the immunosuppressive cytokine. Additional evidence suggests that IL10 single nucleotide polymorphism (SNP) variants are associated with basal cell carcinoma alongside with DNA repair gene variants and also with genes such as iNOS that is associated with prostate cancer recurrence (Dluzniewski et al , 2012; Festa et al , 2005). Since the relationship between IL10 and the DNA damage response is unclear, future studies will require molecular and biochemical characterization of this pathway.…”
Section: Tumor Microenvironment Inflammation and Dna Repairmentioning
confidence: 99%
“…1 article was exclude since it mainly discussed IL-1B and PCa aggressiveness (Zabaleta et al, 2009). 1 article was exclude since it mainly discussed IL-1B and PCa recurrence (Dluzniewski et al, 2012). The other article was exclude since it mainly discussed IL-1B and fatigue in PCa patients treated with androgen deprivation therapy (Jim et al, 2012).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Study carried out by Agalliu I, et al [17] suggested a positive relationship between GSTM1 polymorphism and BCR while others did not comply with their findings [15], [16]. The influence of GSTP1 polymorphism on BCR has also been shown to have inconsistent findings [15]–[18] (Table 1). However, these inconsistent results may due to the limited cases included and/or the potential differences in ethnicity across these studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, these inconsistent results may due to the limited cases included and/or the potential differences in ethnicity across these studies. For instance, study by Cotignola J, et al [15] included only 105 patients; even for the largest studies, there are only 968 patients included [18]. So a meta-analysis of these studies is needed to yield more comprehensive understanding of GSTs polymorphisms on PCa prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation